Possible medium and long range effects of depleted U-238 used in ammunition - Synodinou, B. M.; Papazoglou, I. A. (HNPS Advances in Nuclear Physics, 2019)
In recent years a new type of ammunition has been included in the modern arsenals of Western countries. Depleted Uranium is used in the AlO’s 30-mm gun and in a large variety of other projectiles used by Army, the Marines and Aviation. Due to the radioactive nature of this type of ammunition, it is important to know the distance of dispersion of the material produced. On account of its probable usage some hundred of km north from Greece we are interested in the evaluation of its impact on Greece. We assumed an amount of DU, equal to that daily released during the Gulf War, as being released in South Yugoslavia (Pristina). We examined the possibility of its transport to Greece at a distance more than 150 km far from the release point. For concentration, deposition, dose estimations and health effects evaluation COSYMA code is used. We assumed constant north winds of 5 m/s of speed, no rain, a mixing height equal to about 1000 m and D atmospheric stability conditions. Moreover taking account of the real wind situation during March and April 1999, we calculated the probable impact of daily releases, on selected days, to regions of Greece affected by air masses movement. The results indicate that in spite of the big amount considered as released in a single site, in no cases there has been found any appreciable radiological health effect.